2022
DOI: 10.1177/17407745221136970
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive screening considerations for psychosocial clinical trials in HIV, aging, and cognition

Abstract: Cognitive impairment is a common comorbidity among individuals aging with HIV, which can be an extreme source of stress and anxiety for many. Psychosocial interventions have the potential to alleviate symptoms associated with cognitive impairment and help improve the quality of life of people with HIV as they continue to age; these interventions are in the infancy of development and require further testing via clinical trials. The slow development of interventions may be partially attributed to a common trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Based on our team’s experience piloting the in-person CRGT RCT and our combined years of research and practice, we have identified that a clinical diagnosis of HIV-associated neurocognitive disorder (HAND) may be a barrier to participation in CRGT. As such, a brief screen of cognition may be a more suitable entry condition with the option of referral to HAND testing upon completion of the intervention (Eaton et al, in press). Exploring the receptivity of this proposed process by people aging with HIV and cognitive concerns in focus groups will be important to determining a suitable, community-driven study design for the efficacy RCT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our team’s experience piloting the in-person CRGT RCT and our combined years of research and practice, we have identified that a clinical diagnosis of HIV-associated neurocognitive disorder (HAND) may be a barrier to participation in CRGT. As such, a brief screen of cognition may be a more suitable entry condition with the option of referral to HAND testing upon completion of the intervention (Eaton et al, in press). Exploring the receptivity of this proposed process by people aging with HIV and cognitive concerns in focus groups will be important to determining a suitable, community-driven study design for the efficacy RCT.…”
Section: Methodsmentioning
confidence: 99%
“…However, the small sample size ( n = 12) limited the conclusions we could draw from the pilot. It was predominantly due to participants being required to have a formal HAND diagnosis, which is difficult to conclude (Eaton et al, in press; Ramirez-Garcia et al, 2019). That, by itself, limited our sampling frame to 40 individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these strategies have been individually found helpful amongst people living with HIV [24,25] Results showed that CRGT performed better or equal to mutual aid on outcomes of feasibility, acceptability, fidelity, stress, anxiety, and coping [20,21]. However, the pilot small sample size (n=12) -which was chiefly due to the requirement that participants be formally diagnosed with HAND, a condition that is difficult to determine [26]-limited the conclusions that could be drawn from the results, encouraged consideration of alternative cognitive screens, and necessitated a sufficiently powered trial to determine efficacy. Moreover, the onset of the COVID-19 pandemic ceased all in-person group therapy at the time; and since then, psychosocial interventions are increasingly being adapted as online or hybrid initiatives, and these shifts in healthcare delivery formats appear to be persisting [27,28].…”
Section: Cognitive Remediation Group Therapy (Crgt)mentioning
confidence: 99%
“… 23 , 24 However, the pilot utilized a small sample size ( n =12), which was chiefly due to the requirement that participants be formally diagnosed with HAND, a condition that is difficult to determine. 29 The small sample limited the conclusions that could be drawn from the results and encouraged consideration of alternative screening measure for cognition. Consequently, a sufficiently powered trial was needed after the pilot to determine intervention efficacy.…”
Section: Introductionmentioning
confidence: 99%